A One-step strategy to target essential factors with auxin-inducible degron system in mouse embryonic stem cells - Li, Jingsheng; Dai, Chunhong; Xie, Wenyan; Zhang, Heyao; Huang, Xin; Chronis, Constantinos; Ye, Ying; Zhang, Wensheng (Frontiers in Cell and Developmental Biology, 2022)
The self-renewal and pluripotency of embryonic stem cells (ESCs) are conferred by networks including transcription factors and histone modifiers. The Auxin-Induced Degron (AID) system can rapidly and reversibly degrade its target proteins and is becoming a powerful tool to explore novel function of key pluripotent and histone modifier genes in ESCs. However, the low biallelic tagging efficiency and a basal degradation level of the current AID systems deem it unsuitable to target key pluripotent genes with tightly controlled expression levels. Here, we develop a one-step strategy to successfully target and repress the endogenous pluripotent genes in mouse ESCs and replace their expression with AID fused transgenes. Therefore, this work provides an efficient way for employing the AID system to uncover novel function of essential pluripotent and chromatin modifier genes in ESCs.